Compliance cost under the monthly tax deduction (MTD) scheme for SMEs in Malaysia - Mansor, Muzainah (Quest Journals Inc., 2017)
Monthly Tax Deduction (MTD) Scheme was first introduced in Malaysia in 1995. The aim is to ensure an efficient manner of collecting tax from employees through salary deductions by employers. However, since its introduction, little is known about the implementation of MTD.As far as this study is concerned, there is no published study on the compliance cost borne by the employers under the administration of the MTD scheme.The importance of investigating the compliance cost of the MTD in Malaysia is further emphasised when the Budget 2014 proposed to make MTD for salaried employees a final tax. This scheme will be conducted in stages and is voluntary in nature. The administrative burden of the tax authority will be lightened as it is shifted to the employers.It is therefore the objective of this study to find out the compliance cost borne by the employers under the MTD scheme. The focus is on the employers of the Small and Medium Enterprises (SMEs) as this is the group of employers who bears particularly high tax compliance costs as indicated by the literature. The findings from this study have shown that smaller size SMEs incurred a high compliance cost compared to larger size SMEs.This study has provided essential information to policy makers to help lower the burden of employers when MTD becomes the final tax.In addition, the result also points to the associated costs that are currently faced by the employers of SMEs in trying to comply with the MTD scheme